2006
DOI: 10.4269/ajtmh.2006.74.335
|View full text |Cite
|
Sign up to set email alerts
|

A Drug-Based Intervention Study on the Importance of Buffaloes for Human Schistosoma Japonicum Infection Around Poyang Lake, People’s Republic of China

Abstract: Schistosomiasis japonica is a zoonosis of major public health importance in southern China. We undertook a drug intervention to test the hypothesis that buffalo are major reservoirs for human infection in the marshlands/lake areas, where one million people are infected. We compared human and buffalo infection rates and intensity in an intervention village (Jishan), where humans and buffalo were treated with praziquantel, and a control village (Hexi), where only humans were treated, in the Poyang Lake region. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 11 publications
3
113
2
1
Order By: Relevance
“…However, as depicted in Figures 2a-2c, there is a tendency of reduction both in the Spearman correlation coefficients and in the slope of the linear regression (from 0.395 in 1989 to 0.215 in 2004). The fact that bovines play a major role in the transmission of human schistosomiasis in China is supported by mathematical modelling (Williams et al, 2002), as well as by a recently completed intervention study where either humans alone or humans plus buffaloes were treated with praziquantel (Guo et al, 2006). The implications for schistosomiasis control, including development of a bovine vaccine, have been discussed (Guo et al, 2006;McManus and Dalton, 2006).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, as depicted in Figures 2a-2c, there is a tendency of reduction both in the Spearman correlation coefficients and in the slope of the linear regression (from 0.395 in 1989 to 0.215 in 2004). The fact that bovines play a major role in the transmission of human schistosomiasis in China is supported by mathematical modelling (Williams et al, 2002), as well as by a recently completed intervention study where either humans alone or humans plus buffaloes were treated with praziquantel (Guo et al, 2006). The implications for schistosomiasis control, including development of a bovine vaccine, have been discussed (Guo et al, 2006;McManus and Dalton, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…The fact that bovines play a major role in the transmission of human schistosomiasis in China is supported by mathematical modelling (Williams et al, 2002), as well as by a recently completed intervention study where either humans alone or humans plus buffaloes were treated with praziquantel (Guo et al, 2006). The implications for schistosomiasis control, including development of a bovine vaccine, have been discussed (Guo et al, 2006;McManus and Dalton, 2006). The evidence linking the contribution to transmission by domestic animals points to the looming threat of decreasing returns from human chemotherapy, as the higher the prevalence among domestic animals the higher the risk of infection for humans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of these migrants will be engaged in daily activities such as agriculture, fishing, and reed cutting and will unavoidably have contact with water infested with schistosome cercariae. A recent drug-based intervention study showed that water buffaloes are the major host reservoir for transmission of S. japonicum to humans in the lake region of China and account for ≈80% of transmission; the highest numbers of eggs were released into the environment by young buffaloes <1 year of age ( 24 ). The use of domesticated buffaloes as working animals by farmers will continue to provide reservoirs for S. japonicum .…”
Section: Water Management Projects and Schistosomiasis Transmissionmentioning
confidence: 99%
“…There are three main species of schistosomes infecting humans, Schistosoma mansoni, endemic to Africa, the Middle East, and South America, S. haematobium endemic to Africa, and S. japonicum, endemic to regions of South East Asia specifically in China, the Philippines and Indonesia. Schistosomiasis japonica, caused by S. japonicum, is a zoonosis with water buffaloes and other bovines being major reservoirs for human infection in both China and the Philippines, significantly complicating the control and elimination of the disease Gordon et al, 2012;Gray et al, 2009;Guo et al, 2006). The World Health Organisation (WHO) strategic plan for 2012-2020 has determined that the goal of elimination of schistosomiasis, as a public health problem, is possible by 2025(WHO, 2013.…”
Section: Introductionmentioning
confidence: 99%